Catalogue communities: Work and consumption in the UK catalogue industry. (November 2015) - Casey, Emma
This article offers a sociological understanding of the role of catalogue shopping in women's everyday lives. The article draws on qualitative data generated from interviews with women working at the returns department of the Kays catalogue warehouse in Worcester. During the time of writing, Shop Direct, owners of Kays closed down the historic warehouse in Worcester, effectively bringing over 200 years of Worcester's association with Kays and the catalogue industry to an end, and leading to 500 job losses, including those of the women taking part in the research. Once the largest private employer in Worcester, Kays occupies an important role in local cultural and social identities, and in this article, I will argue that a sociological account of catalogue shopping is apt and timely given such significant social changes, the recent economic downturn and social problems that have long been associated with this form of consumption. In addition, the article will show that to date, much research into catalogue shopping has tended to rest on economic historical accounts of the 'mail order' industry. In contrast, this article argues that catalogue shopping occupies not only a significant place in the popular cultural imagination surrounding the shopping habits of the working classes (and especially working-class women) but has also played a crucial role in women's management of the home, caring for the family and safeguarding an often limited financial budget. The article will consider the important role that catalogues have played in offering credit to working-class women who may have previously struggled to get this. Finally, it adds to recent attempts to put women's domestic consumption patterns firmly on the academic agenda.